2015
DOI: 10.1139/cjm-2015-0017
|View full text |Cite
|
Sign up to set email alerts
|

New report of additional enterobacterial species causing wilt in West Bengal, India

Abstract: Ralstonia solanacearum is known to be the most prominent causal agent of bacterial wilt worldwide. It has a wide host range comprising solanaceous and nonsolanaceous plants. Typical symptoms of the disease are leaf wilt, browning of vascular tissues, and collapsing of the plant. With the objective of studying the diversity of pathogens causing bacterial wilt in West Bengal, we collected samples of diseased symptomatic crops and adjacent symptomatic and asymptomatic weeds from widespread locations in West Benga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 19 publications
1
12
0
Order By: Relevance
“…The bacteria observed under the scanning electron microscope were rod shaped with 0.5-0.9 × 1.2-1.92 µm size. The bacterial cells were larger compared to the sizes reported for Ralstonia solanacearum (Anjali 2019;Sarkar and Chaudhuri 2015).…”
mentioning
confidence: 63%
See 2 more Smart Citations
“…The bacteria observed under the scanning electron microscope were rod shaped with 0.5-0.9 × 1.2-1.92 µm size. The bacterial cells were larger compared to the sizes reported for Ralstonia solanacearum (Anjali 2019;Sarkar and Chaudhuri 2015).…”
mentioning
confidence: 63%
“…Bacterial wilt causes huge losses in many crops (Thakur et al 2014;Mathew 2020) and R. solanacearum has been considered as the causal agent until it was reported that the wilt in tomato is caused by E. cloacae (Sarkar and Chaudhuri 2015). Based on the nearly similar wilting symptoms and previous reports (Álvarez et al 2010), pathogen causing the wilt in marigold was thought to be R. solanacearum (Umesh et al 2018).…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…irrigation water, budding, grafting, ornamental tubers, potatoes, vegetables and banana (Flores-Cruz and Allen, 2009) but the most damaging source of dispersal is waterways (Elphinstone, 2005). The bacterium enters through natural openings and moves towards the xylem vessels where it blocks the supply of minerals and water and causes vascular browning, yellowing and stunting in many plants (Smith, 1920;Sarkar and Chaudhuri, 2015). Other symptoms include narrow dark strips beneath the epidermis, growth of adventitious roots on the stem, epinasty beneath the leaves, and oozing of bacteria in the form of slimy material when the infected stem is cut (Sarkar and Chaudhuri, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The bacterium enters through natural openings and moves towards the xylem vessels where it blocks the supply of minerals and water and causes vascular browning, yellowing and stunting in many plants (Smith, 1920;Sarkar and Chaudhuri, 2015). Other symptoms include narrow dark strips beneath the epidermis, growth of adventitious roots on the stem, epinasty beneath the leaves, and oozing of bacteria in the form of slimy material when the infected stem is cut (Sarkar and Chaudhuri, 2015). The bacterium causes bacterial wilt which is a destructive disease of many plants and has caused significant yield losses in solanaceous crops worldwide (Yabuuchi et al, 1995;Hayward et al, 2005).…”
Section: Introductionmentioning
confidence: 99%